To promote the Interest and Security of the North West Company: Canada's Fur Trade and the War of 1812 - Morrison, Jean (Ontario History, 2012)
While the traditionally-known elements of the War of 1812 deserve recognition, they are not the whole story. The British fought to save the Canadas from conquest by the Americans, but they also strove to save and expand the territorial base of the fur trade, a vital element in the British North American economy, a goal shared by the North West Company. Since Fort William was located in Upper Canada and many NWC actions took place in Upper Canada, the roles of both the Company and the Fort are an integral part of Ontario history. This article examines actions at Sault Ste. Marie, the roles of the schooners Nancy and Perseverance, the development of Yonge Street and the route from Lake Simcoe to Wasaga, the struggle to maintain the fur trade canoe route between Fort William and Montreal, NWC involvement in the taking of Prairie du Chien and the decision made to take Astoria from the American Fur Company which led to British rule over the Columbia Department on the Pacific coast.